Strategi Peningkatan Kualitas Pelayanan Sertifikasi Tanah di Kantor Pertanahan Kabupaten Mandailing Natal Kecamatan Panyabungan - Paisal Rahmat; Lely Afriani; Ummi Hannum; Emelia Anjani; Mulyadi Hakim; Ahmad Faisal Tanjung; Amir Husin (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze strategies for improving the quality of land certification services at the Kantor Pertanahan Kabupaten Mandailing Natal. Land certification services constitute an important form of public service in ensuring legal certainty of land ownership rights for the community. In practice, there are still various administrative, technical, and social challenges that affect service effectiveness. Therefore, appropriate strategies are required to enhance service quality so that it becomes more effective, efficient, transparent, and accountable. This research employs a qualitative method with a descriptive approach. The findings indicate that strategies to improve service quality are implemented through three main aspects: organizational structure development, simplification of service systems and procedures, and strengthening of service culture. Organizational structure development is carried out through a clear division of duties and functions in accordance with job descriptions. The simplification of systems and procedures is implemented through the application of Standard Operating Procedures (SOPs) and the provision of transparent administrative requirement information. Meanwhile, strengthening service culture is reflected in the friendly, responsive, and professional attitude of employees in serving the public.